Improving the competitiveness of agricultural activity in the reformed Common Agricultural Policy – selected legal issues - Lipińska, Izabela (Przegląd Prawa Rolnego, 2021)
The article covers issues related to the implementation of the Common Agricultural Policy reform aimed at strengthening profitability and improving competitiveness of agriculture. Its aim is to assess the legal instruments proposed at the EU level in this respect and to determine whether the adopted normative solutions can serve to improve the profitability of domestic agricultural producers. In conclusion it is stated that the reform provides for a number of instruments that influence the development of competitiveness in agriculture and thereby improve the profitability of the agricultural business. Their implementation results both from the directions of the reform formulated with a view of meeting the needs of the sector, as well as from international obligations and the adopted European Green Deal Strategy. However, although the incentives created prompt the agricultural producers to modify their production methods and ways or activities undertaken in the fields related to agriculture, the strengthening of their market position depends on their operation.